1989
DOI: 10.1002/ajp.1350170203
|View full text |Cite
|
Sign up to set email alerts
|

Forelimb dimensions and goniometry of the wrist and fingers in tufted capuchin monkeys (Cebus apella): Developmental and comparative aspects

Abstract: Adult capuchin monkeys use precision grips during manipulation of small objects, although their thumbs have been classified as pseudo-opposable. We investigated the physical properties of the hands to increase our understanding of manual function in capuchins. Forelimb dimensions and joint mobility (goniometric) measurements were obtained from adult, juvenile, and infant tufted capuchins (Cebus upella). Compared to adult squirrel monkeys, adult capuchins exhibited less flexibility of the wrist and digits. Capu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…On average, over the first three years of life manual phalangeal indices declined by approximately 11% from their initial values at birth (Table 3). Similarly, Fragaszy, Adams-Curtis, Baer, and Carlson- Lammers (1989) found that the external length of the third ray, relative to that of the palm, was greatest in neonatal S. apella and decreased into adulthood. Ontogenetic declines in phalangeal indices were similar across the two capuchin species, in spite of documented differences in foraging strategy between "gracile" capuchins (i.e., Cebus) and "robust" capuchins (i.e., Sapajus) (Alfaro et al, 2012).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…On average, over the first three years of life manual phalangeal indices declined by approximately 11% from their initial values at birth (Table 3). Similarly, Fragaszy, Adams-Curtis, Baer, and Carlson- Lammers (1989) found that the external length of the third ray, relative to that of the palm, was greatest in neonatal S. apella and decreased into adulthood. Ontogenetic declines in phalangeal indices were similar across the two capuchin species, in spite of documented differences in foraging strategy between "gracile" capuchins (i.e., Cebus) and "robust" capuchins (i.e., Sapajus) (Alfaro et al, 2012).…”
Section: Discussionmentioning
confidence: 82%
“…On average, over the first three years of life manual phalangeal indices declined by approximately 11% from their initial values at birth (Table 3). Similarly, Fragaszy, Adams-Curtis, Baer, and Carlson- Lammers (1989) found that the external length of the third ray, relative to that of the palm, was greatest in neonatal S. apella and decreased into adulthood. By three years of age, mean capuchin phalangeal indices for the third manual ray (as a representative digit) was 139%, within the range of values published previously for other adult cebid monkeys (i.e., Saimiri: 145%; Saguinus:…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…A rotational movement of the wrist and forearm toward the radial side of the hand was noted more often in association with power than with precision grips. Overall, these data indicate that capuchins possess a high flexibility of the carpal joints [Fragaszy et al, 1989] that allows them to execute radio/ulnar movements of the wrist during their dexterous prehensile activities. This pattern is well developed in macaque monkeys [Christel & Billard, 2002].…”
Section: Discussion Extracting Behaviormentioning
confidence: 99%
“…Wooden balls (1.27 cm diameter) were presented. One ball was roughly one quarter the width of a capuchin's palm (Fragaszy, Adams‐Curtis, Baer, & Carlson‐Lammers, 1989). Balls were painted with acrylic paint (red, blue, yellow, green), and coated in polyurethane (Figure 2).…”
Section: Study 1 Methodsmentioning
confidence: 99%